The concept of barrier free in healthcare spaces: Labour delivery room design case study - Mohd Nawawi, Norwina (2011)
Healthcare spaces is one of the earliest spaces where barrier free concept of space design is being accepted and regularised as part of the essential building requirement. Spaces in healthcare buildings support activities that support the function of making ease in the delivery of care to sustain live and care for the decease. The paper introduces the subject of healthcare spaces and through case study illustrate step by step how designers – architects and the user clients approach design of the space, using the various available guidelines to produce the first draft drawing, conduct post occupancy evaluation (POE) and following analysis of POE adapt the design for approval and construction. For the purpose of demonstrating the concept of barrier free in healthcare spaces, labour delivery room designs of several hospitals are being selected as the case study. A qualitative research approach was adopted for this study. Literature review on the process of design and activities of labour were conducted prior visits to selected facilities for observation on its usage. Interview of the main players in the design decisions were made pre and post visit where relevant. The paper concluded that this is one of the many spaces in healthcare buildings that support the process of healing or bearable for many ailments and diseases that address physical and mental condition of a person. Each space has its own general and specific requirements to which designers need to understand and provide as appropriate. Barrier free concept is not only for the disable but for the able to support the disable at the time of crisis.